2017
DOI: 10.1002/ejp.1124
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐year prevalence of mental disorders in patients presenting with chronic pain in secondary care: A register linkage cohort study

Abstract: Prevalence rates of anxiety and depression diagnosed by psychiatrists in patients with chronic pain were found to be lower than previous findings using screening instruments. Adjustment disorders were the most frequent disorders diagnosed, as this study is the first to investigate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
1
14
1
1
Order By: Relevance
“…Chronic pain conditions are associated with an elevated risk of suicide, probably due to pain combined with depression and/or substance use disorders (6,8,27). A previous study investigating prevalence of mental disorders in the same population as in this study found in comparison with the general population significantly higher rates of anxiety and depression, and only the males had a higher rate of substance abuse disorders (28). The latter finding might indicate that men tend to cope with somatic symptoms with self-medication through alcohol (29), which may contribute to the increased suicide risk in males.…”
Section: Potential Explanations For Excess Mortality In Patients Withmentioning
confidence: 46%
“…Chronic pain conditions are associated with an elevated risk of suicide, probably due to pain combined with depression and/or substance use disorders (6,8,27). A previous study investigating prevalence of mental disorders in the same population as in this study found in comparison with the general population significantly higher rates of anxiety and depression, and only the males had a higher rate of substance abuse disorders (28). The latter finding might indicate that men tend to cope with somatic symptoms with self-medication through alcohol (29), which may contribute to the increased suicide risk in males.…”
Section: Potential Explanations For Excess Mortality In Patients Withmentioning
confidence: 46%
“…multivariable model 2). The presence of certain comorbidities in the present study to a great extent depended on diagnoses made by physicians, and a recent report indicates that the prevalence of clinically assessed depression and anxiety are, in fact, relatively low compared with reported depressive and anxiety symptoms (74). The time investigated might be of importance as to whether these comorbidities, as well as the other investigator factors, are predictors.…”
Section: Strenghts and Limitationsmentioning
confidence: 57%
“…Moreover, male gender was overrepresented in the most severe group of depressive symptoms. In a Danish register linkage study of patients attending a pain specialist clinic, men had higher prevalence of depression and anxiety disorders 58. In the SQRP, women were obviously overrepresented at the specialist level, a finding also reported in the Danish study 58.…”
Section: Discussionmentioning
confidence: 68%
“…In a Danish register linkage study of patients attending a pain specialist clinic, men had higher prevalence of depression and anxiety disorders 58. In the SQRP, women were obviously overrepresented at the specialist level, a finding also reported in the Danish study 58. The higher proportion of women could be due to factors such as women, compared with men, had a higher prevalence of chronic pain,59,60 different severity (eg, with respect to spreading of pain), and different societal selection mechanisms for treatment and rehabilitation.…”
Section: Discussionmentioning
confidence: 99%